Correlation of spouses’ body weight (results of a 15-year prospective study) - I. V. Dolgalev; V. V. Obraztsov; I. V. Tsimbalyuk; V. A. Seryakova; A. K. Zapodovnikov; B. A. Trotsenko; R. S. Karpov (Кардиоваскулярная терапия и профилактика)
Aim. To study the cross-sectional prevalence of overweight (OW) in men and women, in regard to their spouses’ body weight (BW), as well as to assess the BW dynamics in participants and their spouses over 15 years of the prospective follow-up. Material and methods. In the screening study, body mass index (BMI) was assessed in 425 married couples. The repeat assessment, performed 15 years later, included 232 couples who were still married. OW was diagnosed in subjects with BMI ≥25 kg/m2. Results. In the wives of OW men, OW prevalence was higher (76,2%) than in the spouses of non-OW men (61,3%; p<0,001). In the husbands of OW women, OW prevalence was also higher (61,3%) than in the spouses of non-OW women (43,8%; p<0,001). In the prospective study, the participants with no OW at baseline, whose spouses developed OW, the incidence of OW was significantly higher (60,9%) than in participants whose spouses remained non-OW (16,4%; p<0,001), or in participants whose spouses remained OW (31,7%; p<0,05). Among men and women with OW at baseline, whose spouses reduced their BW and became non-OW, BW normalization was more frequent (32,0%) than in the participants whose spouses either remained OW (9,1%; p<0,001), or remained nonOW (3,4%; p<0,001), or increased BW and became OW (6,9%; p<0,05). Conclusion. BW dynamics in spouses was characterized by parallel increases or decreases, due to shared social and intra-familial factors.